(untitled) (Research, Society and Development, 2020)
The objective of this study is to present the age group of family farmers in Amazonas, as well as participation by gender based on the 2017 Census of Agriculture. It is a challenge to make approaches regarding family farming, and much more challenging is do this exercise regarding Amazonian family farming. Since one of the main motivators of land occupation mobilizations has been to provide food, focusing on this aspect of “who” is behind the scenes of this productivity, is something relevant. The data obtained for the discussion are extracted from the Brazilian Institute of Geography and Statistics (IBGE). There is also a brief presentation of the theory that covers the theme, as well as the issues pertinent to the state of Amazonas and its performance in family farming. The results show that the state has shown significant performance. They show that the age group with the greatest participation in the activity is that of farmers between 45 and 55 years old and between 55 and 65 years old, but that young strength is present in this field. They also reveal that although the countryside, rural areas are predominantly male, there is significant female participation in this thematic.